2012
DOI: 10.1002/qre.1449
|View full text |Cite
|
Sign up to set email alerts
|

Supplier Selection Critical Decision Values for Processes with Multiple Independent Lines

Abstract: The process yield is the most common criterion considered for decision making in supplier selection problem. For normally distributed processes with multiple independent lines, the SpkM index provides an exact measurement for the overall yield. Therefore, the SpkM index can be implemented to deal with the supplier selection problem with processes having multiple independent lines. In this article, a test statistic obtained by a division method is employed to establish a hypothesis testing procedure, with two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…For processes with multiple independent lines, Pearn and Wu and Pearn et al developed 2‐supplier selection procedures based on the yield index SpkM using division method and subtraction method, respectively. However, the 2 research works focus on 2 suppliers' selections.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For processes with multiple independent lines, Pearn and Wu and Pearn et al developed 2‐supplier selection procedures based on the yield index SpkM using division method and subtraction method, respectively. However, the 2 research works focus on 2 suppliers' selections.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These studies are listed in Table 3. Pearn and Wu (2013) utilised overall yield indices to deal with the supplier selection problem. Wu et al (2008) developed a practical procedure based on process capability indices to make supplier selection decisions between two given suppliers.…”
Section: Process Capability Indicesmentioning
confidence: 99%
“…Chen and Chen (2006), Wu et al (2008), Pearn and Wu (2013), Wu, Liao, and Yang (2013), Wu, Pearn, and Chuang (2013) • An effective and convenient tool for evaluating quality performance. • Provides a numerical and unitless measure of whether a process can produce the required quality specified by the product designer.…”
Section: Process Capability Indicesmentioning
confidence: 99%
“…Two methods such as the difference test statistic and the ratio test statistic can be used to solve this comparison problem. Some studies dealing with two‐supplier selection using process capability index can be found in the literature . Recently, Wang presented the difference test statistic to compare two suppliers for linear profiles.…”
Section: Introductionmentioning
confidence: 99%